Clay mineralogical characteristics and the palaeoclimatic significance of a Holocene to Late Middle Pleistocene loess–palaeosol sequence from Chaoyang, China. (17th October 2016) - Sun, Zhong-Xiu; Wang, Qiu-Bing; Han, Chun-Lan; Zhang, Qing-Jie; Owens, Phillip R.
ABSTRACT: Changes in soil chemistry in response to varying climatic regimes can alter the equilibria of soil systems and result in different clay minerals. Variations in phyllosilicate clay composition can reflect temporal and spatial climatic changes, such as summer/winter monsoon cycles. The objective of this research was to investigate the mineralogy of the clay fractions as a proxy for determining variations in the East Asian monsoon climate, based on a section at Chaoyang in China spanning the last 0.423 Ma BP. The clay mineralogy record in the Chaoyang section was compared with other proxies as recorded in this section and with other palaeoclimatic indicators, including oxygen isotopes from oceanic sediments and loess–palaeosol sections on the Chinese Loess Plateau (CLP). The results from clay mineralogy and related climatic studies show that the summer monsoon has a trend of four increased stages and four decreased stages; whereas the winter monsoon displays the opposite trend. During the last 0.423 Ma BP, the strongest winter monsoon occurred around 0.243–0.311 Ma BP. During this period, which included an intense winter monsoon, the soil in the section had the least illite, one of the smallest kaolinite and illite/Chlorite (I/C) indices and an overall decreasing clay content. The period 0.225–0.243 Ma BP had the strongest summer monsoon over the last 0.423 Ma BP. This period had the greatest amount of illite, the highest I/C index, greater overall clay content and the strongest magnetic susceptibility signal. Additionally, this section contained the smallest mean grain size. The multi-monsoon climate cycles of alternating cold-dry and warm-moist conditions as recorded in the Chaoyang section corresponded well with multiple glaciation cycles based on deep sea sediments. This indicates that the Chaoyang section provides a record of palaeoclimate changes in northeast China that can be linked to mineralogical suites to assist in reconstructing the palaeoclimate over the Late Middle Pleistocene, and complements the global palaeoclimate records in the CLP.